Germination and gametophyte development of Cyathea corcovadensis (Raddi) Domin (Cyatheaceae) from spores stored at low temperatures - Marcon, Catiuscia; Silveira, Tatieli; Droste, Annette (Acta Scientiarum. Biological Sciences, 2014)
The tree fern Cyathea corcovadensis (Raddi) Domin is an endangered species in the state of Rio Grande do Sul, Brazil. It currently occurs only in the northern segment of the coastal region. Spore storage would help in conservation programs since it maintains genetic variability and provides material for in vitro cultures. Current study evaluates the effect of low temperatures combined to different spore storage times on the germination and initial gametophyte development of C. corcovadensis. Spores were divided into two groups: spores of the first group were sowed immediately in Meyer culture medium with nystatin, at pH 4.0, while spores of the second group were stored at 7, -20 and -196°C during 60, 120, 180, and 365 days and then sowed in the same medium. Spore storage at 7 and -196°C for 365 days not only provided higher germination percentages than those reported for recently-collected spores but also stimulated gametophytic development. The latter was demonstrated by the higher percentages of laminar gametophytes in these treatments. The possibility of storing spores provides material for in vitro experiments, which is of special interest for C. corcovadensis due to its ornamental potential and conservation status.